Systém controllingu zodpovedného podnikania na báze alternatívnych koncepcií zodpovedného podnikania - Dubcová, Gabriela; Foltínová, Alžbeta (Univerzita Pardubice, 2010)
Corporate controlling system, tools of the corporate responsibility controlling, conceptions of the corporate responsibility controlling, GRI a G3, VeriSEAAR (Social and Ethical Accounting, Auditing and Reporting), Investors in People (certificate IIP), BPCB (Business Principles for Countering Bribery), Transparency International tools - TI Six Step Process and SEM (Self-Evaluation Module), ISO 14000 and EMAS, ISO 26000, AA 1000, SA8000, GoodCorporation Standard, OECD Guidelines for Multinational Enterprises, system’s structure of the corporate responsibility controlling on the G3 basis.
Keywords: corporate controlling system; tools of the corporate responsibility controlling; conceptions of the corporate responsibility controlling; standards of the corporate responsibility controlling